2021
DOI: 10.3390/atmos12121555
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Atmospheric Photochemical Evolution of the Organic Component of Biomass Burning Aerosol on Its Radiative Forcing Efficiency: A Box Model Analysis

Abstract: We present the first box model simulation results aimed at identification of possible effects of the atmospheric photochemical evolution of the organic component of biomass burning (BB) aerosol on the aerosol radiative forcing (ARF) and its efficiency (ARFE). The simulations of the dynamics of the optical characteristics of the organic aerosol (OA) were performed using a simple parameterization developed within the volatility basis set framework and adapted to simulate the multiday BB aerosol evolution in idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…Previous studies have investigated the phase behavior of some types of atmospheric aerosol particles, such as mixtures of secondary organic aerosol with inorganic salts and mixtures of secondary organic aerosol with hydrocarbon-like organic aerosol. However, the phase behavior of primary BBOA remains understudied and unresolved. Models simulating the microphysics, chemical evolution, concentration, or radiative properties of wildfire smoke typically assume that BBOA comprises only a single phase. , On the other hand, Jahn et al identified that some sampled BBOA particles exhibited an organic shell coating an organic core using transmission electron microscopy images, with the caveat that the vacuum conditions required for this type of microscopy may affect the particle morphology. In addition, bulk-phase liquid tar condensates generated from high-temperature wood distillation were reported to have separated into a water-soluble and nonsoluble oily phase, , although it is not known whether phase separation would occur in particles containing this material after equilibration with ambient relative humidity (RH).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated the phase behavior of some types of atmospheric aerosol particles, such as mixtures of secondary organic aerosol with inorganic salts and mixtures of secondary organic aerosol with hydrocarbon-like organic aerosol. However, the phase behavior of primary BBOA remains understudied and unresolved. Models simulating the microphysics, chemical evolution, concentration, or radiative properties of wildfire smoke typically assume that BBOA comprises only a single phase. , On the other hand, Jahn et al identified that some sampled BBOA particles exhibited an organic shell coating an organic core using transmission electron microscopy images, with the caveat that the vacuum conditions required for this type of microscopy may affect the particle morphology. In addition, bulk-phase liquid tar condensates generated from high-temperature wood distillation were reported to have separated into a water-soluble and nonsoluble oily phase, , although it is not known whether phase separation would occur in particles containing this material after equilibration with ambient relative humidity (RH).…”
Section: Introductionmentioning
confidence: 99%
“…As an integral part of atmospheric aerosol, smoke particles significantly affect the environment and human health 1,[9][10][11][12][13][14][15][16][17][18][19] . Scattering and absorbing optical radiation, smoke aerosol participates in the formation of the radiation budget of the atmosphere and the Earth's surface, affects the state of the weather and climatic processes [20][21][22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…44 Hettiyadura et al and Li et al have both shown that tar condensates from both burning and O2-free pyrolysis of wood separate into immiscible aqueous and oily liquid phases. 45,46 Despite the above, models simulating the chemistry, transport, and climatic impacts of wildfire BBOA typically assume that BBOA comprises only a single phase. 37,[47][48][49] Our understanding of the viscosity and phase behaviour of BBOA remains incomplete, in part, because previous studies have focused on samples generated in the laboratory and not collected from the real atmosphere.…”
Section: Introductionmentioning
confidence: 99%